A Study on Price Behavior of Crude Oil, Gold, Nifty and India VIX” Multivariate Analysis - Dr. Asifulla A.; H Mahaboob Basha (International Journal of Engineering and Management Research, 2023)
Gold and Crude oil are very vital global Variables and they are ruling the market. An increase in the worldwide oil prices and gold prices hurts the Indian economy. To know whether there is any dependency of gold and crude oil price fluctuations with respect to Indian market. The interdependence between financial markets and financial products are the most difficult problems for investors. The volatility of one market can influence the value index of another marketplace. The purpose of this article is to examine whether the price of gold, the price of oil, the volatility of the price of gold (GVZ), and the volatility of the price of oil (OVX) have a major collision on the stock index (GSPC). The goal is to find coexistence between characters, determinants, and price levels. The survey has taken into explanation of the prices of gold and oil business on the Commodity Exchange (MCX) between 1 January 2014 and 31 December 2018. This relationship is analyzed using tendency line assessment. The gold-oil ratio is calculated as the ratio of gold price to crude oil price related to time. Correlation tests are also performed to discover the strong point of the relationship between the prices of the two products. In the commodity market, in most cases, gold and crude oil price groups are moving in the same direction. Therefore, it is recommended to buy and sell gold and crude oil at the same time. So the risk can be minimized. Sometimes gold and crude oil prices will go in the opposite direction. Gold prices can be very tight and crude oil can go down. At that point, it is advisable to invest in the declining products. It is likely that the prices of falling items will soar automatically.